(untitled) (Applied Biological Research, 2023)
In field conditions such as forest ranges, movement corridors or in areas prone to man animal conflict very often the only evidence/specimens available for investigation are animal scat, fur, hairs, epidermis, etc. Since animal scat contains denuded intestinal epithelial cells it can provide genetic material which can be used for further analysis and other downstream studies. In present study surface scrapings from faecal samples of 5 different carnivore species viz., tiger (Panthera tigris), lion (P. leo), leopard (P. pardus), domestic dog (Canis familiaris) and domestic cat (Felis catus) were collected for DNA extraction using standard kit based protocols. A fragment of 16S rRNA gene of mitochondrial DNA was amplified using specific primers. The amplicons generated were subjected to restriction digestion. Species identification and differentiation was done using fragment length polymorphism (PCR-RFLP). The results depicted the utility and effectiveness of molecular scatology based PCR-RFLP technique for identification of wild carnivore species in forensic investigations. The observations also highlighted the potential of highly conserved mitochondrial DNA markers like 16SrRNA gene to be employed for species identification and differentiation of wild carnivores.